A mulher no discurso da ex-ministra Damares Alves: uma análise dos imaginários sociodiscursivos - Corrêa, Ana Laura da Silva (2023)
This research, which falls under the Semiolinguistic perspective of Discourse Analysis, aims to identify the socio-discursive imaginaries engendered from the social representations of women present in the discourse of the former Minister of Women, Family, and Human Rights, Damares Alves. The specific objectives are to investigate how social representations of women are established and characterized in the speeches of Damares Alves, to analyze the relationships established between these social representations and the feminist theories of Silvia Federici and Heleieth Saffioti, and finally, to identify which socio-discursive imaginaries are engendered from the social representations present in the speeches of the former minister. To achieve these objectives, a qualitative approach is used, drawing on the Semiolinguistic perspective of Discourse Analysis, particularly with Patrick Charaudeau (1999, 2007, 2011, 2017, 2018, 2019), and the notions of social representations and socio-discursive imaginaries that underpin the analysis. In addition, the theoretical foundations of philosopher Silvia Federici (2017, 2019), a Marxist feminist, and sociologist Heleieth Saffioti (1976), who provide a historical perspective on women, indicating the obstacles present in this trajectory, are used. The analysis focuses on news published by the Metrópoles and R7 portals, given the relevance of journalistic discourse. Initially, an analysis is carried out concerning the communication contract in order to explain the production conditions under which the analysis was developed. A predominance of the capture perspective is identified, with the reproduction of belief knowledge taken up by the enunciator in the title and lead of the articles, so that the informative content takes a back seat. In the analysis concerning the identification of social representations and socio-discursive imaginaries taken up in the enunciator's speech, four main imaginaries are identified, each associated with different social representations: 1) in the sexist imaginary: the representations of the sentimental woman, the princess woman, and the homemaker woman; 2) in the patriarchal imaginary: the obedient woman, the woman taken care of by men; 3) in the nationalist imaginary: the woman who contributes to the development of her own country; and finally, 4) in the conservative imaginary: the heterosexual woman, the woman against abortion and feminism. The observations made in the analysis are in line with the theories brought by Federici (2017) and Saffioti (1976).